2017
DOI: 10.2147/ott.s145072
|View full text |Cite
|
Sign up to set email alerts
|

S100A16, a promising candidate as a prognostic marker for platinum-based adjuvant chemotherapy in resected lung adenocarcinoma

Abstract: PurposeAlthough cisplatin-based adjuvant chemotherapy improves the survival of patients with resected non-small-cell lung cancer, not all patients show a survival benefit, and some patients experience severe toxicity. Therefore, identifying biomarkers is important for selecting subgroups of patients who may show improved survival with platinum-based adjuvant chemotherapy. S100A16 is thought to play key roles during different steps of tumor progression. The aim of this study was to evaluate the use of S100A16 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 28 publications
(31 reference statements)
3
16
1
Order By: Relevance
“…Thus, S100A16 expression was set as a continuous variable in COX survival analysis. The following univariate and multivariate analysis confirmed the independent prognostic value of S 100A16 expression in terms of OS, which is consistent with the findings in two recent studies [ 7 , 8 ]. In addition, we also found that increased S100A16 expression was an independent prognostic indicator of unfavorable RFS (HR: 1.206, 95%CI: 1.045–1.393, p = 0.011), after adjustment of pathologic stage and residual tumors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, S100A16 expression was set as a continuous variable in COX survival analysis. The following univariate and multivariate analysis confirmed the independent prognostic value of S 100A16 expression in terms of OS, which is consistent with the findings in two recent studies [ 7 , 8 ]. In addition, we also found that increased S100A16 expression was an independent prognostic indicator of unfavorable RFS (HR: 1.206, 95%CI: 1.045–1.393, p = 0.011), after adjustment of pathologic stage and residual tumors.…”
Section: Discussionsupporting
confidence: 91%
“…In colorectal cancer, membrane S100A16 expression might serve as an independent prognostic marker for overall survival (OS) [ 6 ]. Two recent studies (N = 170 and N = 65 respectively) observed that S100A16 is significantly upregulated in lung adenocarcinoma (LUAD) and might be an independent prognostic indicator of poor OS [ 7 , 8 ]. However, the small sample size limits their statistical power.…”
Section: Introductionmentioning
confidence: 99%
“…S100A16 was a recent addition to the S100 family that isolated from astrocytoma [61]. The expression of S100A16 was upregulated in various tumors, such as bladder, lung, thyroid gland, pancreas, and so on [62, 63]. In lung adenocarcinoma, S100A16 expression was associated with vessel invasion and poor outcome and confirmed as an independent prognostic marker [62].…”
Section: Discussionmentioning
confidence: 99%
“…Its abnormal expression could be found in lung cancer [21]. Specifically, high S100A16 expression was found to be significantly associated with a poor prognosis in lung cancer [22][23][24]. FGF2, also known as a basic fibroblast growth factor (FGF), is an important regulator of cell growth and differentiation under physiological and pathological conditions [25,26].…”
Section: International Journal Of Genomicsmentioning
confidence: 99%